Examining the Factors That Influence Customers’ Intention to Use Ar-Rahnu at Post Office: A Case Study of Kedah - Baharum, Nadiah Nabilah; Maamor, Selamah; Othman, Azizah (IBTRA, 2015)
One of the familiar Islamic banking and finance products used for short-term collateralized borrowing is Islamic pawn broking or also known as ar-rahnuin Malaysia. The rapid growth of ar-rahnu in term of profit and beneficial to customer attract many organizations to offer this kind of product as an alternative to conventional pawnshop. In 2013, Pos Malaysia Berhad as one of the famous premier postal service providers in Malaysia offered ar-rahnu which called Ar- Rahnu@ POS. Since ar-rahnu is a new product that offered by an organization that is not familiar with Islamic finance product, therefore, this study aims to inspect the customer’s intention to use Ar-Ar-Rahnu @ POS. This study based on survey conducted at Post Office in the state of Kedah. A survey comprised of 200 respondents was carried out. A structured question was designed where the data was analyzed by correlation Pearson and multi regression analysis. Results show that customer service is the most influential variable on customer’s intention to use Ar- Rahnu @ POS while syariah view, attitude and pricing give a moderate impact. It is recommended that Post Office should do aggressive promotion, improve customer service, make clear and transparent transaction that based on Islamic principle and offer different and attractive package in order to attract new customer